Response about the Importance of Digital Marketing Skills for Vocational Teachers - Firdaus, Firdaus; Wahyuni, Sungkem Tri; Risdianto, Eko (CV Media Inti Teknologi, 2022)
This study aims to analyze responses about the importance of digital marketing skills for vocational teachers. This type of research is survey research using quantitative research methods. The sample in this study were 41 teachers at SMKN 2 North Bengkulu. The research was conducted in November 2022. The data collection technique used a questionnaire so that the measuring tool was a questionnaire made with a modified Likert scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. The results of the study show that digital marketing skills are important for vocational teachers.